2023
DOI: 10.3390/insects14050419
|View full text |Cite
|
Sign up to set email alerts
|

Is Integrated Management of Gymnandrosoma aurantianum Possible with Trichogramma atopovirilia and Novel Products Used in Citrus Orchards in Brazil?

Abstract: In Brazil, the citrus fruit borer, Gymnandrosoma aurantianum Lima, 1927, is a serious pest in orange orchards, causing an annual loss of 80 million US dollars, and is managed with multiple insecticide applications, often 56 in a single season. On the other hand, the parasitoid wasp Trichogramma atopovirilia Oatman & Platner, 1983 has the potential for controlling G. aurantianum by attacking its eggs. Considering the intensive insecticide applications in citrus orchards in Brazil to control the large comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…However, interestingly, insecticide treatments in vineyards using cyantraniliprole could be compatible with field releases of the parasitoid T. evanescens. Similar to our results, cyantraniliprole was also considered selective (harmless) to adults of T. atopovirilia [48]. As such, chlorantraniliprole, another diamide insecticide, did not significantly affect the survival of T. pretiosum adult parasitoids, whereas the neonicotinoid insecticide acetamiprid caused 82% mortality in T. pretiosum adults within 24 h of exposure to dried pesticide residues [53].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, interestingly, insecticide treatments in vineyards using cyantraniliprole could be compatible with field releases of the parasitoid T. evanescens. Similar to our results, cyantraniliprole was also considered selective (harmless) to adults of T. atopovirilia [48]. As such, chlorantraniliprole, another diamide insecticide, did not significantly affect the survival of T. pretiosum adult parasitoids, whereas the neonicotinoid insecticide acetamiprid caused 82% mortality in T. pretiosum adults within 24 h of exposure to dried pesticide residues [53].…”
Section: Discussionsupporting
confidence: 88%
“…More specifically, the lowest percentages of T. evanescens emergence at both 3 and 7 days after treatment were obtained when pupae were treated with the neonicotinoid insecticide acetamiprid compared with the pesticides flupyradifurone, lambda-cyhalothrin, and spiroxamine. Previous laboratory experiments also demonstrated that cyantraniliprole is selective (harmless) to pupae of another Trichogramma parasitoid, T. atopovirilia Oatman and Platner [48]. However, according to Saber [49], similar to our results on the higher toxicity of acetamiprid to pupae, imidacloprid, another neonicotinoid insecticide, significantly affected the emergence of T. cacoeciae Marchal from the pupal stage residing inside S. cerealella parasitized eggs.…”
Section: Discussionsupporting
confidence: 87%